1992
DOI: 10.1111/j.1365-3083.1992.tb02833.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Immune Response to Hepatitis B Virus and Human Serum Albumin. III. Induction of Anti‐Albumin Antibody Secretion In Vitro by C‐Gene‐Derived Proteins in Peripheral B Cells from Chronic Carriers of HBsAg

Abstract: The circulatory pool of B cells from the majority (11/13) of chronic hepatitis B surface antigen (HBsAg) carriers contained sensitized B cells with the capacity to secrete IgG antibodies with specificity for human serum albumin (HSA), when stimulated with E. coli-derived core protein at low concentrations in vitro. The IgG anti-HSA secretion was dependent upon and regulated by T cells, and optimal secretion was obtained at T/B-cell ratios of 1.0-4.0, varying for different individuals. The level of anti-HSA sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The fact that all relative autoantibody titres exceeded normal values to the degree of hypergammaglobulinaemia suggests their clustered up-regulation. Hence, up-regulation of anti-albumin antibodies in our patient differs from that observed in patients with chronic hepatitis B, where antibodies to monomeric albumin are selectively up-regulated (11).…”
Section: Discussionmentioning
confidence: 81%
“…The fact that all relative autoantibody titres exceeded normal values to the degree of hypergammaglobulinaemia suggests their clustered up-regulation. Hence, up-regulation of anti-albumin antibodies in our patient differs from that observed in patients with chronic hepatitis B, where antibodies to monomeric albumin are selectively up-regulated (11).…”
Section: Discussionmentioning
confidence: 81%
“…Supporting this contention, it was shown that the levels of anti‐albumin IgG autoantibodies were higher than normal in both acute and chronic hepatitis patients, but that those levels decreased to normal when the patients recovered . It was also shown that the circulatory pool of B cells from the majority of chronic hepatitis B surface antigen carriers contained sensitized B cells that, when stimulated, secreted IgG antibodies with specificity for human serum albumin .…”
Section: Discussionmentioning
confidence: 99%